2014
DOI: 10.1007/s00455-013-9511-8
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Characteristics of Health-Related Quality-of-Life Questionnaires in Oropharyngeal Dysphagia

Abstract: Dysphagia can have severe consequences for the patient's health, influencing health-related quality of life (HRQoL). Sound psychometric properties of HRQoL questionnaires are a precondition for assessing the impact of dysphagia, the focus of this study, resulting in recommendations for the appropriate use of these questionnaires in both clinical practice and research contexts. We performed a systematic review starting with a search for and retrieval of all full-text articles on the development of HRQoL questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
87
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(90 citation statements)
references
References 49 publications
1
87
0
2
Order By: Relevance
“…In older persons, in particular, OD may cause fatal complications, such as aspiration pneumonia and suffocation, or lead to undernutrition due to decreased oral intake or decreased mental activity [9,10]. Therefore, caution is required in the early phase of OD in older patients.…”
Section: Introductionmentioning
confidence: 99%
“…In older persons, in particular, OD may cause fatal complications, such as aspiration pneumonia and suffocation, or lead to undernutrition due to decreased oral intake or decreased mental activity [9,10]. Therefore, caution is required in the early phase of OD in older patients.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic literature reviews have been published on the psychometric properties of oropharyngeal dysphagia screening [8, 9] and HR-QoL questionnaires [10] but not on FHS questionnaires.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of DBS on swallowing is a complicated but important matter to address, as DBS brings a clear-cut improvement in cardinal symptoms of PD, but does not seem to have the same pronounced effect on swallowing function 23 . Swallowing function can be assessed by using fiber endoscopy, video fluoroscopy, or patient selfreports 13,16,29 . Traditionally, little attention has been given to patients' subjective experience, even though it has been shown that the feelings and attitudes towards swallowing and eating of patients with PD affect both their eating habits and their mental well-being 13,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, little attention has been given to patients' subjective experience, even though it has been shown that the feelings and attitudes towards swallowing and eating of patients with PD affect both their eating habits and their mental well-being 13,16 . However, over the last few years, several self-report assessment scales have been suggested to supplement the clinical examination of swallowing function 29,30 . Such selfreport questionnaires encompass the patients' own perception of their condition, and hence could be argued to reduce possible observer bias.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation